2020
DOI: 10.1111/itor.12877
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pricing and production decisions of fashion apparel brands in a two‐stage sales setting

Abstract: Clothing is a typical seasonal and fashionable product; it is very easy to cause inventory backlog problems. This paper addresses the determination of pricing and production of a fashion clothing brand under both presale and regular sales stages. More specifically, we analyze the effect of the fashion degree of clothing and price on the demand. Demand during different market periods (peak sales season, low sales season, and stable market) change with time. The static pricing decision of presale price is made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Referring to Shi et al (2021) [34], market demand is a function of the product price, VAS level, and fashion rate of the product, i.e., D(p, S, t)…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to Shi et al (2021) [34], market demand is a function of the product price, VAS level, and fashion rate of the product, i.e., D(p, S, t)…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…(1) For a two-echelon fashion product CBEC supply chain dominated by the integrated OWLP, when the demand rate is considered the impact of VAS level in addition to retail price, fashion rate (Shi et al, 2021) [34] with the additive form rather than the multiplicative form (Cai et [35][36][37]. What are the optimal product pricing, the optimal logistics pricing, and the optimal VAS level?…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars focus on the pricing of traditional enterprises, such as S. W. Lin and Januardi. (2022), Huang et al (2022), andShi et al (2020). However, with the rapid development of platform economy, the pricing decision of ride-hailing platforms has become a hot topic in the field of operation management (J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choi et al (2020) used the mean risk theory to analyze and explore how the customer's risk attitude affects the optimal service pricing decision, and indicted that the best service price will decrease (increase) if consumers are more risk-averse. Shi et al (2021) investigated the optimal pricing and productions decisions for fashion apparel brands, and showed that a dynamic pricing policy should be adopted when the market size is stable rather a static price strategy. Unlike earlier research, this paper introduces spatial distance preferences of logistics service demanders and providers in the single-homing and competitive bottleneck models, and studies the impact on the pricing strategy of two competing logistics platforms.…”
Section: Literature Reviewmentioning
confidence: 99%